2019
DOI: 10.17219/dmp/100386
|View full text |Cite
|
Sign up to set email alerts
|

Er:YAG and diode laser application in implant bed preparation and implant uncovering: A case report

Abstract: The use of lasers in the field of dentistry has increased recently. Their numerous advantages and applications in soft and hard tissue surgeries make them a great alternative to conservative methods in dental implantology. The most commonly used lasers are diode and erbium-doped yttrium aluminium garnet (Er:YAG) lasers. The Er:YAG laser can be used in implant bed preparation, as it brings no thermal injury to the bone. The laser does not cause bone necrosis and positively affects osseointegration and the heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In recent years, studies in dental implantology using the Er:YAG laser have demonstrated an extremely favorable effect on osseointegration. Rapid healing processes and accelerated osseointegration have been observed [39,52].…”
Section: Laser Technologymentioning
confidence: 99%
“…In recent years, studies in dental implantology using the Er:YAG laser have demonstrated an extremely favorable effect on osseointegration. Rapid healing processes and accelerated osseointegration have been observed [39,52].…”
Section: Laser Technologymentioning
confidence: 99%
“…In the last few decades, different approaches were proposed in order to ameliorate dental treatments. [1][2][3][4][5][6][7][8][9] The use of implants to rehabilitate maxillary and mandibular edentulous areas has become a common practice worldwide, with reliable long-term results. In different clinical situations, a lack of supporting bone as a result of physiologic bone rearrangement, surgical trauma, or delayed restoration, generates problems in implant insertions.…”
Section: Introductionmentioning
confidence: 99%